Analysis of Stock Valuation of PT Amman Mineral, Tbk. as a Basis for Investment Decision Making - Khawas, Fawwas Amal; Nurjannah, Nurjannah; Munawir, Munawir (Entrepreneurship, Management, and Business Research Journal, 2025)
This study aims to determine and analyse how much the stock valuation of PT Amman Mineral, Tbk. during Q2-2023, Q3-2023, Q4-2023, Q1-2024 and to determine and analyse whether the stock valuation of PT Amman Mineral, Tbk. is overvalued, fair valued and undervalued. The analysis method used is the stock valuation ratio. The data used is secondary data derived from the annual financial report data of PT Amman Mineral, Tbk. taken from the official website https://www.amman.co.id The results showed that the shares of PT Amman Mineral, Tbk. in Q2-2023, Q3-2023, Q4-2023, Q1-2024 were in an Overvalued condition, namely the shares were in an expensive or high condition, so potential investors are advised not to buy because the shares are valued at a high price by the market while it is recommended that investors sell them.